Effect of speed-jump training on volleyball specific measurements skills in female athletes - Kleinwolterink, A.; Moody, S.; Mayhew, J. (The Journal of Strength and Conditioning Research, 2010)
A major objective in volleyball training is to increase vertical jump height and jump speed. Various training approaches have been attempted to enhance the specificity of training for these elements of the game. Further investigation is needed to determine the degree to which selected jump training techniques might enhance game-specific performance. The purpose of this study was to determine the effect of speed-jump training on countermovement vertical jump (CMJ), 3-step approach vertical jump (AVJ), standing blocking transition jump (SBTJ), and approach blocking transition jump (ABTJ). Female volleyball players (n = 21, age 15-21 yrs) served as subjects. Prior to training, each athlete was measured for maximum CMJ and AVJ using a vertical pole with moveable veins that measure vertical touch height. The training program consisted of performing 4 sets of 4 reactive jumps and was performed 3X/week for 6 weeks on an automated jump mat that recorded ground reaction time and the average of the 4 jumps. During training, each athlete attempted to perform her jumps as quickly as possible while maintaining an average jump height of at least 85% of their best CMJ. Following training, players improved significantly in CMJ (20.0 +/- 2.3 to 21.0 +/- 2.2 ins), AVJ (21.9 +/- 3.1 to 23.0 +/- 2.8 ins), SBTJ (17.7 +/- 2.9 to 20.0 +/- 2.4 ins), and ABTJ (20.8 +/- 3.3 to 22.4 +/- 2.8 ins). The relative increase in SBTJ (14.0 +/- 8.9%) was significantly greater than for ABTJ (9.1 +/- 9.6%), AVJ (5.9 +/- 8.2%), and (4.8 +/- 4.2%), with no significant difference noted among the latter. It appears that concentrating on quickness in jump training while attempting to maintain a near-maximal effort can produce improvements in both jumping performance and game-specific quickness.